2022
DOI: 10.3390/su14031878
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Risk of Acute Gastrointestinal Disease Attributed to E. coli O157:H7 in Irrigation Water and Agricultural Soil: A Quantitative Microbial Risk Assessment

Abstract: Introduction: The occurrence of E. coli O157:H7 in the agricultural environment poses a serious threat to public health. The primary aim was to estimate the probability of illness caused by E. coli O157:H7 in irrigation water and agricultural soil niches. Methods: The Quantitative Microbial Risk Assessment was used and the risks were characterized using the Monte Carlo simulation with 10,000 iterations. Results: The mean levels of E. coli O157:H7 in the irrigation water and agricultural soil samples was 1.328 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Thus, in recent years, researchers have come to realize the importance of the relationship between EE and EI. Some studies pointed out the positive impact of EE on students' EI (Iwu et al, 2021;Wu et al, 2022), however, other studies indicated the opposite situation, when EE failed to promote the EI of the students surveyed. (Nabi et al, 2018).…”
Section: Entrepreneurial Education (Ee)mentioning
confidence: 99%
“…Thus, in recent years, researchers have come to realize the importance of the relationship between EE and EI. Some studies pointed out the positive impact of EE on students' EI (Iwu et al, 2021;Wu et al, 2022), however, other studies indicated the opposite situation, when EE failed to promote the EI of the students surveyed. (Nabi et al, 2018).…”
Section: Entrepreneurial Education (Ee)mentioning
confidence: 99%